Research priorities relating to the delivery of cardiovascular prevention and rehabilitation programmes: results of a modified Delphi process. Issue 1 (3rd April 2023) - McHale, Sheona; Cowie, Aynsley; Brown, Sarah; Butler, Tom; Carver, Kathryn; Dalal, Hasnain M; Dawkes, Susan; Deighan, Carolyn; Doherty, Patrick; Evans, Jo; Hinton, Sally; Jones, Jennifer; et al.
Abstract : Objective: The purpose of this British Association for Cardiovascular Prevention and Rehabilitation (BACPR) research priority setting project (PSP) was to identify a top 10 list of priority research questions for cardiovascular prevention and rehabilitation (CVPR). Methods: The PSP was facilitated by the BACPR clinical study group (CSG), which integrates as part of the British Heart Foundation Clinical Research Collaborative. Following a literature review to identify unanswered research questions, modified Delphi methods were used to engage CVPR-informed expert stakeholders, patients, partners and conference delegates in ranking the relevance of research questions during three rounds of an anonymous e-survey. In the first survey, unanswered questions from the literature review were ranked and respondents proposed additional questions. In the second survey, these new questions were ranked. Prioritised questions from surveys 1 and 2 were incorporated in a third/final e-survey used to identify the top 10 list. Results: From 459 responses across the global CVPR community, a final top 10 list of questions were distilled from an overall bank of 76 (61 from the current evidence base and a further 15 from respondents). These were grouped across five broad categories: access and remote delivery, exercise and physical activity, optimising programme outcomes, psychosocial health and impact of the pandemic. Conclusions: This PSP used a modified Delphi methodology to engage the international CVPR community to generate a top 10 list of research priorities within the field. These prioritised questions will directly inform future national and international CVPR research supported by the BACPR CSG.